Development of a miniature point source pyroshock simulator. (1st September 2020) - Hwang, Dae-Hyun; Park, Hyun-Su; Han, Jae-Hung
Abstract: Pyrotechnic devices have been widely utilized in various applications: spacecraft, launch vehicles, missiles, and aircraft as well as for stage separation, valve control, and booster separation. However, most pyrotechnic separators generate an intensive mechanical transient response called pyroshock, which can cause catastrophic failures in electronic equipment. In order to validate that the structure or equipment can withstand the generated shock level, pyroshock tests should be performed with properly simulated structural configurations and the shock sources. Most of the previous pyroshock simulators using mechanical excitation have been developed as shock table configurations; they can effectively apply the target shock levels to the test component. However, it is difficult to simulate the pyroshock source in practical structures. In this study, a miniature pyroshock simulator that can easily replace a pyrotechnic device and is adaptable onto the most practical structures was developed. A disk resonator is introduced to control the shock response by changing the first natural frequency of the disk resonator. To excite the disk resonator, we devised a launch device that effectively controls the impact velocity with easy reloading capability. Experiments for 27 different conditions were conducted to identify the control parameters for the shock levels. The developed simulator also showed high repeatability, and it is easy to prepare repeated experiments using the developed shock simulator. This device can easily generate the simulated point-source pyroshock for real structures such as an assembled spacecraft.